Optimization of Factory Location Selection Using the AHP Method Based on Operational Cost Criteria, Logistics Accessibility, and Labor Availability - Angger Styo Yuniarti; Muhammad Arif Kurniawan; Andi Rukmana; Samsul Makin (Jurnal Info Sains : Informatika dan Sains, 2026)
Factory location selection represents a strategic decision that significantly impacts the long-term operational success of manufacturing companies. This research aims to optimize the factory location selection decision-making process by applying the Analytical Hierarchy Process method, considering three fundamental criteria: operational costs, logistics accessibility, and labor availability. A quantitative approach was employed involving five expert respondents consisting of industrial practitioners and academics to conduct pairwise comparison assessments of four alternative industrial estate locations in West Java. The analysis results indicate that operational costs have the highest priority weight of 0.540, followed by logistics accessibility with a weight of 0.297, and labor availability with a weight of 0.163. Cikampek Industrial Estate emerged as the optimal location with a global priority weight of 0.300, excelling in operational cost efficiency despite having limitations in logistics accessibility. Consistency testing shows Consistency Ratio values ranging from 0.035 to 0.046, confirming the validity of respondent assessments. This research provides practical contributions in the form of a structured decision model that can assist manufacturing company management in making strategic production facility location decisions more objectively and measurably.